VOLUME DAN FREKUENSI APLIKASI PGPR AKAR BAMBU TERHADAP PERTUMBUHAN BIBIT TEBU (Saccharum officinarum L.) SINGLE BUD CHIPS - Sopiana Sopiana; Beny Setiawan; Rosmalinda Rosmalinda; Nurhayati Nurhayati (Journal of Agro Plantation (JAP), 2022)
ABSTRAC Provision of seeds with the single bud chips method has the benefit of being more efficient in reducing the area of ​​the nursery. In order to support the growth of single bud chips sugarcane seedlings in nurseries, bamboo root PGPR was given which made it easier for P to dissolve in the soil so that it was easily absorbed by plant roots. P element in the soil is needed by plants to meet plant nutrition so that if the P element needs are met, the plant will grow well. This study aims to determine the volume, frequency of application and interaction of bamboo root PGPR on the growth of single bud chips sugarcane seedlings. The study used a factorial Completely Randomized Design (CRD) with 15 treatments and 3 replications. The first factor is the volume of PGPR bamboo roots (K) which consists of five levels as follows: K0 = control/without PGPR, K1 = PGPR volume 5 mL/tan, K2 = PGPR volume 10 mL/tan, K3 = PGPR volume 15 mL /tan, K4 = Volume of PGPR 20 mL/tan. The second factor is the frequency of application (F) which consists of three levels as follows: F0 = 1 watering, F1 = 2 watering, F2 = 3 watering. The volume of PGPR bamboo roots as much as 15 mL/plant with a frequency of PGPR application of 2 times watering is the optimal provision for the growth of single bud chips sugarcane seedlings. Keyword : Frequency, Sugarcane, Volume